2019
DOI: 10.1094/phyto-05-18-0152-r
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Magnesium Oxide: A Novel Bactericide Against Copper-Tolerant Xanthomonas perforans Causing Tomato Bacterial Spot

Abstract: Bacterial spot caused by Xanthomonas perforans causes significant damage on tomatoes in Florida. Due to the presence of copper (Cu)-tolerant X. perforans strains, Cu bactericides are not effective in disease management. Hence, there is a critical need to find alternatives for Cu. Anti-bacterial activity of magnesium oxide (Nano-MgO), and other metal oxide nanoparticles, were evaluated against a Cu-tolerant and sensitive X. perforans strain. In vitro experiments demon-strated high antibacterial activity of Nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 42 publications
(46 reference statements)
1
36
0
Order By: Relevance
“…This can be achieved in part by understanding the structural and biochemical changes on bacterial cells by nanoparticle exposure. Epifluorescence microscopy has previously provided insight into whether the nano materials are bactericidal or bacteriostatic in nature 26 . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) have been shown to provide information on structural modifications on the surface and interior of bacterial cells upon exposure to the Cu/Zn hybrid nanoparticles 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved in part by understanding the structural and biochemical changes on bacterial cells by nanoparticle exposure. Epifluorescence microscopy has previously provided insight into whether the nano materials are bactericidal or bacteriostatic in nature 26 . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) have been shown to provide information on structural modifications on the surface and interior of bacterial cells upon exposure to the Cu/Zn hybrid nanoparticles 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Various antibacterial nanoparticles have been developed and studied for disease management of copper-tolerant Xanthomonas spp. 8,2326 . For example, the use of silver (Ag) nanoparticles merged in a dsDNA-graphene oxide matrix (Ag-dsDNA-GO).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in nanoparticle technology should enable effective modification resulting in a more potent product. Accordingly, different metal-ion-based nanoparticles have been successfully utilised as antimicrobial compound in greenhouse and field trials against tomato infecting Xanthomonas strains (Ocsoy et al 2013;Paret et al 2013;Makarovsky et al 2018;Liao et al 2019).…”
Section: Application Of Bactericides and Biocontrol Agentsmentioning
confidence: 99%
“…Metallic nanoparticles (NPs) such as silver, zinc and copper oxide, among others, have proven to inhibit the growth of phytopathogenic viruses, fungi and bacteria, demonstrating the enormous potential that NPs have to formulate new and advanced commercial antimicrobial agents (Yah & Simate, 2015). Current research has demonstrated that metallic NPs have an active bactericidal effect against plant pathogenic strains such as P. syringae, C. michiganensis (Banik & Luque, 2017;Cumplido-Nájera et al, 2019) as well as Xanthomonas perforans (Liao et al, 2018). The effectiveness of NPs depends on their size and shape.…”
mentioning
confidence: 99%